2016
DOI: 10.1016/j.entcs.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Into the Square: On the Complexity of Some Quadratic-time Solvable Problems

Abstract: International audienceWe analyze several quadratic-time solvable problems, and we show that these problems are not solvable in truly subquadratic time (that is, in time O(n2−ϵ) for some ϵ>0), unless the well known Strong Exponential Time Hypothesis (in short, SETH) is false. In particular, we start from an artificial quadratic-time solvable variation of the k-Sat problem (already introduced and used in the literature) and we will construct a web of Karp reductions, proving that a truly subquadratic-time algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
96
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 39 publications
2
96
0
1
Order By: Relevance
“…For sets of small cardinality, we hash the universe U to a smaller universe, where complementing the sets does not take too much time and space. From this reduction, the claim follows: Claim 4.2 is itself an interesting result: in [11], conditional lower bounds for many problems stem from the above three problems, forming a tree of reductions. By our equivalence, the root of the tree can be replaced by the quadratic-time hardness conjecture on any of the three problems, simplifying the reduction tree.…”
Section: Complementing Sparse Relationsmentioning
confidence: 95%
See 2 more Smart Citations
“…For sets of small cardinality, we hash the universe U to a smaller universe, where complementing the sets does not take too much time and space. From this reduction, the claim follows: Claim 4.2 is itself an interesting result: in [11], conditional lower bounds for many problems stem from the above three problems, forming a tree of reductions. By our equivalence, the root of the tree can be replaced by the quadratic-time hardness conjecture on any of the three problems, simplifying the reduction tree.…”
Section: Complementing Sparse Relationsmentioning
confidence: 95%
“…, n k and n u , and let the input size m (corresponding to the number of edges in the input graph) be the sum of all sets' sizes in all set families. Borassi et al [11] showed that when k = 2, these Basic Problems require time m 2−o(1) under SETH, and that if the size of universe U is poly-logarithmic in the input size, then the three problems are equivalent under subquadratic-time reductions. The main idea of the reductions between these problems is to complement all sets in S 1 , or S 2 , or both.…”
Section: Complementing Sparse Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural approach to prove Radius limitations in sparse graphs is to base them on the OV conjecture. However, such a lower bound has remained elusive [2,16]. This is due to the following type mismatch.…”
mentioning
confidence: 99%
“…Our work is an example of hardness results in P, that is a growing area of research (e.g., see [12]). Roughly, finer-grained notions of reduction between polynomial-time solvable problems are used in order to prove that if A can be reduced to B and B can be solved inÕ(n q−ε )-time 2 then A can also be solved inÕ(n q−ε )-time [43].…”
Section: Introductionmentioning
confidence: 99%